Design Optimisation of a Search and Rescue Micro-Submarine - Muhammad Firdaus, Abong Abdullah; Mastika, Lamat; Abdul Riezal, Dim; Andrew Ragai Henry, Rigit (Universiti Malaysia Sarawak (UNIMAS), 2008)
A micro-submarine (micro-sub) is a very small unmanned submarine, which is normally being deployed for various dangerous underwater tasks effectively with minimum cost and risks. The micro-sub design must be optimised in every aspect of its practicability and operation ability. A combination of industrial design and engineering method is used design the micro-sub. Industrial design method emphasis on application of design aspects that user experience, configuration of sensitive electronics and software unit compartment, and developing the body shell streamline. The final design concept is translated into computer aided design software, Autodesk 3D Max and Catia to generate a 3-D model of the micro-sub. Modifications of the model at this stage are now done virtually. The computer generated model data is then fed to rapid modelling software, 3-D Printer to produce a full scale rapid prototyping model. It is desirable to have a smoother as possible velocity profile around the micro-sub body in order to obtain a better stability and control of the micro-sub, application of engineering method such as flow visualisation is vital to determine the effects of fluid flow conditions around the micro-sub when it submerged in changing underwater current. The 3-D model data is also used to create a computer simulation of the micro-sub in actual underwater environment using a commercially available computational fluid dynamic (CFD) package, Star-CD. The effects of the micro-sub geometry on the velocity and pressure distributions on the micro-sub outer shell surface were tested and analysed for Re = 500,000 and 3,000,000. The analysis output is used to propose further enhancement of the micro-sub with a smoother velocity profile around the body shell. The final design is custom fabricated for field trials and evaluations.